Yamada's atlas of gastroenterology - 4 0 16; M. D. Wang, Timothy C.,;Camilleri, Michael; 5 (Hoboken, NJ : Wiley-Blackwell, 2022)
Yamada's Atlas of Gastroenterology has for 25 years been the most comprehensive, well respected gastroenterology atlas available. It is the perfect supporting Atlas for the main textbook, providing over 2 thousand high quality images fully downloaded via a companion website. The Atlas of Gastroenterology is a gold-standard tool that provides specialists with an outstanding array of images covering all facets of the field. Every GI disorder from liver abscesses, endocrine neoplasms of the pancreas, to motility disorders of the esophagus are fully illustrated through the use of endoscopic ultrasonographs, computed tomography scans, magnetic resonance images, radionuclide images, and angiograms. Access to accurate, high-quality images are vital for ensuring effective management of patients with GI complaints--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: 2 -- 0; 6; Gastrointestinal Diseases -- 20; 20; Atlas -- 2